Computer Vision for Autonomous Drone Video Capture - Heldes, Adrián; Alexa, Štěpán; Karas, Jakub; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2023)
The focus of this master thesis will be on the development of a prototype drone that utilizes computer vision for autonomous video capture. The prototype will be implemented using python for the drone's computer vision code and for the accompanying application. The drone will be able to autonomously follow a person using computer vision algorithms, enabling it to capture dynamic footage. This work aims to demonstrate the potential of computer vision in drones for real-time video capture and tracking, and will contribute to the growing field of drone-based video capture applications.
Vedoucí práce: Štěpán Alexa
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: data a analytika pro business [obor dipl. práce]; diplomové práce; master's theses